PARENTAL AWARENESS ON PRENATAL CONCERNS: AN EDUCATIONAL PERSPECTIVE - Rathee, N. K.; Bajwa, Sukhpal K. (European Scientific Journal, ESJ, 2015)
Having a healthy baby is a dream of every parent and a cherished goal of every nation. However, the latest statistics indicate that in US about one in every 33 babies is born with birth defects or disabilities, and that the birth defects are one of the most leading causes of infant deaths, accounting for more than 20% of all infant deaths. Many of these birth defects or disabilities are avoidable if precautions are taken and care is provided during prenatal period. Awareness among parents about such prenatal concerns is therefore, critical. This exploratory pilot study was conducted to find out the level of basic awareness among parents about prenatal concerns and avoidable factors leading to birth defects and disabilities. The subjects (N= 73) were African American parents residing in the city of Dover and surrounding areas in Delaware State. The subjects were interviewed and administered the Prenatal Concerns Survey designed for this research. The results on various aspects revealed unawareness among parent on many critical issues, and the overall results indicate that 19.4% of the parents expressed ignorance about the basic prenatal concerns. A broad based research is recommended for in-depth analysis.